Investigating the Impact of FDI, Foreign Aid, and Islamic Capital Markets on Carbon Emission in ASEAN: The Moderating Role of Regulatory Quality - Muh Afdhal Mubarak AS; Hikmah Endraswati (Journal of Economics Development Issues, 2023)
In the last few decades, member countries of ASEAN have experienced economic growth driven by increased FDI and FAID. However, the effect of this investment and foreign aid on carbon emissions in ASEAN countries is still not fully understood. This study examines the impact of FDI and FAID on carbon emissions in ASEAN countries, taking into account Regulatory Quality as a moderator. Panel data from 2011 to 2021 was collected using purposive sampling. The results show that FDI significantly and positively affects carbon emissions, while FAID does not show a significant effect. In contrast, the Islamic capital market shows a significant and negative impact on carbon emissions, demonstrating its potential to reduce emissions in ASEAN countries. Regulatory Quality moderates the relationship between FAID and carbon emissions in a positive way. This study recommends strengthening environmental regulations to mitigate the negative effects of FDI while promoting socially and environmentally responsible Islamic capital markets in ASEAN countries. Further research is needed to understand the factors influencing this relationship comprehensively.